The effect of commercially available mouthrinses on the hardness and solubility to light cured composite resins - Bicomong, Clarissa Victoria B.
This three-month long experiment aimed to evaluate the effects of commercial mouthrinses on the hardness and solubility of composite resins (Total Performance Hybrid). Sixteen composite discs were fabricated and randomly divided into eight equal groups. The hardness and weight of all the discs were measured prior to the experiment using a Shore-D-Durometer and analytic balance. Each of the six brands of mouthrinses, distilled water and synthetic saliva (control) were assigned to one group of composite discs, which were then immersed and vibrated in their assigned solutions for a minute twice a day. Measurements were taken and compared at the end of ninety days. Results of the study showed that the mouthrinses do not significantly decrease the hardness nor increase the solubility of light cured composite resins. The Pearson's correlation showed that the alcohol content of the mouthrinses was proportional to the decrease in hardness of light cured composite resins. Therefore, commercially available mouthrinses do not significantly decrease the hardness nor increase the solubility of light cured composite resins after a ninety-day period of two-minute exposures to the mouthrinses. The alcohol content of mouthrinses can directly affect the decrease in hardness, but not the increase in solubility of the light cured composite resins.